Tinjauan Prinsip dan Praktik Kontemporer: Menuju Paradigma Manajemen Bisnis Islam yang Berkelanjutan - Wiyono, Joko (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2025)
This paper aims to critically review the principles and contemporary practices of Islamic business management (IBM) in the context of global challenges and sustainability imperatives. It highlights the relevance of core Islamic values—such as tawhid, justice (?adl), maslahah, and amanah—as the foundation for developing a sustainable business paradigm. Through a literature-based conceptual approach, the study identifies both the potential and constraints of IBM in adapting to dynamic global market structures, the ESG movement, and digital disruption. Findings suggest that while the normative framework of Islamic management offers ethical and sustainable solutions, its implementation requires structural, institutional, and intellectual reform. This paper proposes a renewed paradigm that integrates Islamic moral economy with sustainability science and ethical governance